Perubahan Sosio-Kultur antara Tradisi dan Modernitas: Studi Kasus Tedhak Siten - Zahra, Lailatuz; Alfiyanti, Nur Laili; Mardhiyah, Rahma Annisa; Handayani, Sania Putri; Nabiila, Shaesa Rindini; Shofa, Zahra Amalia; Ediyono, Suryo (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2025)
This research aims to examine the dynamics of socio-cultural change in the implementation of the Tedhak Siten tradition as a form of interaction between local cultural heritage and modernity. Tedhak Siten, as one of the important rituals in the life cycle of Javanese society, has undergone a transformation both in form, meaning, and method of implementation along with the times. The main focus of this research is to identify the forms of socio-cultural changes that occur in the Tedhak Siten tradition, as well as the Javanese community's response to the phenomenon. The method used is a literature study approach with secondary data analysis from journals, scientific articles, and socio-cultural theories. The results concluded that modernization does not completely erode traditional values, but rather encourages the adaptation of forms and reinterpretation of traditions to remain relevant in the midst of modern life. Thus, the preservation of local culture requires a contextual approach that is responsive to social change.